2015
DOI: 10.1016/j.pmn.2015.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Pain Assessment Strategies in Home Care and Nursing Homes in Mid-Norway: A Cross-sectional Survey

Abstract: The prevalence of pain ranges from 27.8% to 86.5% in nursing homes and 42% to 50% in home care. Pain assessment is the first step toward effective pain management. The aim of this study was to explore the use of pain assessment strategies (verbal, numeric, and observation rating scales and standardized questions) in home care and nursing homes. The study was a descriptive cross-sectional survey. Health care providers who were responsible for the patients' medications replied to a questionnaire. In-home care an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…None of the students on this team expressed knowledge of communication with a person with dementia, despite that dementia is included in both nursing and physical therapy curricula. Torvik et al (2015) concluded that the use of pain assessment tools in Norwegian nursing homes appears to be deficient, which the present study also supports. Students on Team I had no knowledge of assessment tools for persons with dementia.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…None of the students on this team expressed knowledge of communication with a person with dementia, despite that dementia is included in both nursing and physical therapy curricula. Torvik et al (2015) concluded that the use of pain assessment tools in Norwegian nursing homes appears to be deficient, which the present study also supports. Students on Team I had no knowledge of assessment tools for persons with dementia.…”
Section: Discussionsupporting
confidence: 80%
“…Thus, pain knowledge may be inconsistent among Norwegian health care students, and pain management in Norwegian nursing homes may be inadequate. Furthermore, health care professionals in Norwegian nursing homes typically lack knowledge regarding pain assessment in the elderly and people with dementia (Torvik, Nordtug, Brenne, & Rognstad, 2015), which emphasizes the need to focus on pain education.…”
Section: Introductionmentioning
confidence: 99%
“…Checklists aim to standardize a process and thus to improve patient outcomes 22. Checklists for preventing risk of falls,23 pressure ulcers,24 pain assessment,25 and surgical safety are well known and widely used in nursing. It is important though to understand that checklists are reminders of what to do.…”
Section: Discussionmentioning
confidence: 99%
“…Over half of the pain intervention studies (n = 13) were related to non-pharmaceutical treatments, and Pain training interventions were examined in 21 papers, and were generally shown to be effective in improving pain management and treatment use/appropriateness ( IncS 19,32,33,39,40,43,63,79,84,87,97). As well as improved pain management, resident quality of care and quality of life also had the potential to be enhanced (IncS 11), which could impact on their longer term wellbeing…”
Section: Interventionsmentioning
confidence: 99%